THE EFFECTIVENESS OF REACT STRATEGY IN WRITING DESCRIPTIVE TEXT OF THE SIXTH GRADE STUDENTS OF SMK BAJIMINASA MAKASSAR - Suryani Syamsuddin (Celebes Education Review, 2021)
This research were aimed to find out whether or not the use of REACT strategy is effective to improve the students’ ability in writing descriptive text of the sixth grade students at SMK BAJIMINASA MAKASSAR and a significant difference of the teaching learning results treated by using REACT strategy and directed instruction. It covered students’ five components of writing (content, organization, vocabulary, language use and mechanics).The research applied Quasi-Experimental design. This research was designed into two groups; Experimental group and Control group. Each group consisted of 32 students. The sample was chosen by using simple random technique that used lottery technique. The experimental class was taught by REACT strategy while control class was taught by directed instruction. The data were collected through subjective writing test both in experimental group and control group namely pretest and posttest. The test was distributed once for both groups before and after treatment. The treatment was conducted for four meetings in experimental group and control group. The data collected through subjective writing test were analyzed by using SPSS 20.0 version. The research findings showed that the use of REACT strategy was higher than that the control group in improving students writing ability. It revealed that the students’ improvement of posttest with mean score 80.91 was better than the mean score of pretest 68.47 in experimental group. The difference of those mean score was significant. It was based on t-test value at significant level 0.05, the P-value was lower than Sig. level (0.000 < 0.05) and the improvement of posttest with mean score 71.75 was better than the mean score of pretest 65.88 in control group, the t-test of significant 2-tailed was lower than alpha (0.025 < 0.05). H1 was accepted and H0 was rejected. It concluded that, REACT strategy gave improvement on students’ writing ability, it was proved by analyzing the students’ pretest and posttest in experimental group. Thus, the implementation of teaching writing ability, the REACT strategy was better or more effective than directed instruction